Design of Circular Patch Array Microstrip Antenna Using Slot for ISM Band - Liya Yusrina Sabila; Anton Yudhana; Muhammad Miftahul Amri; Asra Akrima; Igo Putra Pratama (Journal of Electrical Technology UMY, 2022)
This paper presents a Microstrip Antenna Analysis for the ISM Band with a circular patch design with a radius of 17 mm at a frequency of 2,400 – 2.484 GHz. The fabricated array antenna has a very compact width and length of 9.5 x 7.5 cm each. Therefore, an increase in bandwidth on the monopole antenna can be applied to the array arrangement. So to get the best antenna design, two optimizations of antenna size changes are carried out during the simulation: optimization of patch radius and slot length. The radius variation is used to shift the frequency range and slot length for impedance matching, as seen from the S11 value of less than -10 dB. From each change, the best results are taken. Experiments get the best antenna simulation results and are then fabricated. From the measurement results on the fabricated antenna, the lowest S11 value is -19.602 dB, and the gain is 3.52 dBi. The slot technique's optimization process has successfully shifted the frequency to approximately 100 MHz and increased the bandwidth by about 5% or 40 MHz.